Leafy vegetables for health and nutritional security - Ranjan, PRAGYA; Singh, B. K.; Reddy, Y. S.; Dubey, R. K. (Indian Horticulture, 2019)
Besides common green leafy vegetables, there are large number of underutilized leafy vegetables, which are available seasonally and practically no information is available on their production and quality. Consumption of such vegetables is confined to the people living in the areas where they grow. In fact, these are blessed with a number of surprising virtues which really needs attention by the growers and consumers worldwide in achieving nutritional and health security.